PENINGKATAN HASIL BELAJAR IPA MELALUI METODE DISCOVERY DALAM PEMBELAJARAN DARING PADA SISWA KELAS V SD NEGERI 27 PEKANBARU - Rosmidawati Br Sitinjak (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This research is motivated by the low science learning outcomes of fifth grade students of SD Negeri 27 Pekanbaru. This can be seen from 1) the learning outcomes obtained by students are not optimal, this can be seen from the report card scores, especially in science subjects, most of the students have not reached the specified minimum completeness criteria (KKM), 2) students seem difficult to understand the material presented delivered by the teacher in class and students rarely answer the questions given by the teacher. This study aims to improve science learning outcomes in fifth grade students of SD Negeri 27 Pekanbaru. The subjects of this study were fifth grade students of SD Negeri 27 Pekanbaru with a total of 30 students. The form of research is classroom action research. The research instrument consisted of learning outcomes instruments and data collection instruments in the form of observation sheets for teacher activities and student activities. Based on the results of the analysis and discussion, it can be concluded that the application of the Discovery learning method in online learning can improve learning outcomes in science lessons for fifth grade students at SD Negeri 27 Pekanbaru. This success is evidenced by an increase in learning outcomes before taking action to cycle I and cycle II. Before taking action, student learning outcomes were classified as